New records and check list of arthropods from two oasis ecosystems in Algeria - Nacima DEGHICHE-DIAB; Tesnim DEGHICHE (Studia Universitatis Babeș-Bolyai. Biologia)
An arthropod sampling survey was performed in two palm groves from the wilaya of Biskra and Ouled Djellal. During 12 months (2020) of survey, the obtained results indicated the presence of 117 taxons divided into 2 classes (Insecta =103 species and Arachnids = 11 species). The species belonged to the orders: Coleoptera, Diptera, Orthoptera, and Hymenoptera. The Coleoptera order was the most represented in the two palm groves (32 from Ouled Djellal (OD) and 6 from Feliache (Fe)). The major trophic guild represented in the oasis ecosystems was the predator guild (OD= 39%, Fe=32%) in comparison to those of phytophagous (OD= 28%, Fe=12%) and pests (OD= 4%, Fe=15%). This indicates an ecological balance in the investigated oasis ecosystems between pests and their predators. The observation of two new species: Scymnus frontalis (Fabricius, 1787) and Diomus zinon (González and Honour, 2011), from the Coccinilidae Family increases the number of predator species of insect pests in the investigated oasis ecosystems.